ANALISIS PERUBAHAN LABA KOTOR SEPEDA MOTOR MATIC PADA PT. ASTRA INTERNATIONAL – HSO BALIKPAPAN PERIODE 2015-2017 - , Camelia Verahastuti 3, Isa Kurnia Wijaya Putri LCA. Robin Jonathan (EKONOMIA, 2020)
The purpose of this study was to determine the causes of changes in gross motorbike matic profit at PT. Astra International - HSO Balikpapan for the period of 2015-2017. The theory of this research is cost accounting that focuses on changes in gross profit, by using a change in gross profit analysis, sales price variance, sales quantity or variance volume, cost of sales price variance, and cost of sales quantity on volume variance. The research data needed is 2015-2017. Based on the results of the study showed that the change in gross motorbike matic profit from 2015-2016 was due to increased sales factor of Rp 82,378,005,000 and an increase in cost of sales price variance Rp 55,779,713,690 while for 2016-2017 the sales increased by Rp 242,933.095,000 and cost of sales price variance was Rp. 171,770,796,608.Based on the results of the analysis, the authors can draw several conclusions that causes of changes in the gross profit of automatic motorbikes at PT. Astra International - HSO Balikpapan from 2015 - 2017 is the amount of sales, changes in selling prices, changes in quantity (volume) of cost of goods sold and changes in cost of goods sold, sales have decreased and the cost of goods sold has decreased, so the gross profit will also decrease.